PENDAMPINGAN PRODUKSI PODCAST YOUTUBE UNTUK MENDEKATKAN TEKNOLOGI PADA SISWA MADRASAH NAUNGAN PESANTREN - Robi'ah Machtumah Malayati; Sayidah Afyatul Masruroh (As-Sidanah, 2024)
The Community Service Program (PkM) aims to introduce both the students of Madrasah Aliyah Nurul Qur'an Bendungrejo and the students to technology through the approach of producing content for YouTube podcasts. The PkM also aims to encourage the younger generation to be content producers in the digital era, not just consumers. This PkM is significant because, within the madrasah environment, previous activities have been focused on religious aspects, including limited extracurriculars such as the art of al banjari, khitobah, and qiroah. Hence, this PkM represents an innovative step. Using the Participatory Action Research (PAR) approach, the PkM involves students in identifying problems, seeking solutions, learning, and producing content for YouTube podcasts. The results have shown an improvement in their ability to conceptualize, interact, communicate, and produce content for YouTube podcasts. The PkM successfully enhanced the students' creativity and broadened their insights into opportunities in the digital domain. Sustained efforts are needed to equip the younger generation with relevant competencies to face technological advancements and social changes. This PkM has made a positive contribution by complementing madrasah activities and promoting the increased utilization of technology among both the santri and students.